Numerical simulation of suspension flow with deposition in 3D bifurcated tubes - Serrenho, A. (2012)
This paper addresses the fundamental topic of the effect of geometry upon transport of suspension flow with deposition. The performance of bifurcating tubes designed according to Murray’s law and tubes with arbitrary geometries were compared using a numerical simulation. Flow fields were solved in an Eulerian grid system, and particle trajectories were calculated by the Lagrangian method.